FEATURES OF SUPERFICIAL VEIN THROMBOSIS IN PATIENTS WITH A LARGE DIAMETER OF GREAT SAPHENOUS VEIN - Viktoriia Mishura; Yurii Melekhovets (Eastern Ukrainian Medical Journal, 2022)
Introduction. Superficial vein thrombosis is characterized by the formation of thrombi in the superficial veins with subocclusion or occlusion of the venous lumen and its inflammatory reaction, which occurs more often in the lower extremities. Chronic venous disease in 75–88% of cases is the most important clinically identified factor in the development of superficial vein thrombosis. The great saphenous vein is affected in 60–80% of cases. A population-based study found that the chronic venous disease is a risk factor for venous thromboembolism and correlates with an increased risk of mortality in patients. Venous thromboembolism is a major burden of the disease worldwide, with approximately 10 000 000 cases per year. Objective: to assess the prevalence of superficial vein thrombosis in patients with chronic venous disease and to identify the relationship between the diameter of the great saphenous vein and superficial vein thrombosis. Materials and methods. Total of 925 chronic venous disease cases were analyzed from January 2019 to December 2021 at the Clinical Department of Surgery, Traumatology, Orthopedics, and Phthisiology of Sumy State University (Sumy Laser Clinic, LLC) for the prevalence of superficial vein thrombosis in patients with chronic venous disease who were undergoing treatment. The patients with superficial vein thrombosis were examined for the diameters of great saphenous vein and venous reflux using ultrasound 10 mm below the sapheno-femoral junction, in the upper and lower thirds of the thigh. Results: Of 925 chronic venous disease cases, superficial vein thrombosis was observed in 53 cases, which accounted for 5.73 % of the total. Women accounted for 67.9 % (36), men – for 32.1 % (17). The study included patients aged 25 to 69 years (mean age 52.62 ± 10.48 years). In 69.8 % (37) of superficial vein thrombosis cases, the diameter of great saphenous vein was ≥ 10 mm at a level 10 mm below the sapheno-femoral junction; in 49 % (26) of cases – in the upper third of the thigh; in 30.2 % (16) of cases – in the lower third of the thigh. That is, the extension of the sapheno-femoral junction trunk to the lower third of the thigh was preserved in 43.24% of cases. Conclusion. The results of the study revealed a high prevalence (5.73%) of superficial vein thrombosis. 69.8% of all cases of superficial vein thrombosis was registered in patients with a large diameter (≥ 10 mm) of great saphenous vein.